Dukungan Kelembagaan Agribisnis Terhadap Pengembangan Usahatani Bawang Merah di Desa Bimorejo - Triya Sri Lestari; Diah Puspaningrum (UNEJ e-Proceeding, 2018)
Bimorejo Village was one of the areas which had the most potential to expanse or develop onion agribusiness. Those were seen from the high amount of onion production of the village compared to the other areas located in the same sub-district. It was inseparable from the Institutional Agribusiness from upstream until downstream. However, those institutional agribusiness were not complex enough as there were not any Village Cooperative System (Indonesia: Koperasi Unit Desa) and agroindustry. It was also worsened by the institutions that did not undertake their role in the business, making the support given did not suffice. This research was done to know the reinforcement of the institutional agribusiness towards the expansion of Onion Agribusiness in Bimorejo Village. This research was done in Bimorejo Village using purposive method. This research was designed as a qualitative research with case study method. The sources of the data were chosen by using purposive sampling. The data was collected by using in-depth interview, non-participative observation, and document review. The data was then analyzed by using a method by Miles and Huberman. The validity test was done by using source and technique triangulation. The results of this research showed that the Institutional Agribusiness towards the expansion of onion agribusiness in Bimorejo Village including agriculture store Rukun Tani, Bimalestari farmers association, Tengkulak, Agriculture Counseling Bureau (Indonesia: Balai Penyuluh Pertanian/BPP), HIPPA Bimatirta, irrigation public works department, Bimorejo Village functionaries. The aforementioned support from Institutional Agribusiness could be classified in three forms: Instrumental Support, Emotional Support, and Informational Support.